Shaking Dutch grounds won't shatter the European gas market - Franziska Holz; Hanna Brauers; Philipp M. Richter; Thorsten Roobeek (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The Netherlands have been a pivotal supplier in Western European natural gas markets in the last decades. Recent analyses show that the Netherlands would play an important role in replacing Russian supplies in Germany and France in case of Russian export disruption (Richter & Holz, 2015). However, the Netherlands have suffered from regular earthquakes in recent years that are related to the natural gas production in the major Groningen field. Natural gas production rates- that are politically mandated in the Netherlands - have consequently been substantially reduced, with an estimated annual production 30% below the 2013 level. We implement a realistically low production path for the next decades in the Global Gas Model and analyze the geopolitical impacts. We find that the diversification of the European natural gas imports allows spreading the replacement of Dutch gas over many alternative sources, with diverse pipeline and LNG supplies.There will be hardly any price or demand reduction effect. Even if Russia fails to supply Europe, the additional impact of the lower Dutch production is moderate. Again, alternative suppliers from various sources are able to replace the Dutch volumes. Hence, the European consumers need not to worry about the declining Dutch natural gas production and their security of supplies.
Keywords: C69; L71; Q34; 330; natural gas; supply security; Europe; equilibrium modeling